"Proof Under Reasonable Doubt": Ambiguity of the Norm Violation as Boundary Condition of Third-Party Punishment. (March 2023) - Toribio-Flórez, Daniel; Saße, Julia; Baumert, Anna
In six studies, we consistently observed costly third-party punishment (3PP) to decrease under ambiguity of the norm violation . Our research suggests that, under ambiguity, some people experience concerns about punishing unfairly. Those with higher (vs. lower) other-oriented justice sensitivity (Observer JS) reduced 3PP more pronouncedly (in Studies 1–3 and 4b, but not replicated in Studies 4–5). Moreover, those who decided to resolve the ambiguity (hence, removing the risk of punishing unfairly) exceeded the 3PP observed under no ambiguity (Study 4). However, we did not consistently observe these concerns about punishing unfairly to affect 3PP (Studies 4–5). We further considered whether people could use ambiguity as justification for remaining passive—thus, avoiding the costs of 3PP. We did not find conclusive evidence supporting this notion. Taken together, ambiguity entails a situational boundary of 3PP that sheds light on the prevalence of this behavior and, potentially, on its preceding decision-making.